2008
DOI: 10.1007/s11046-008-9154-8
|View full text |Cite
|
Sign up to set email alerts
|

Candida albicans and Candida tropicalis in Oral Candidosis: Quantitative Analysis, Exoenzyme Activity, and Antifungal Drug Sensitivity

Abstract: Candida albicans and C. tropicalis obtained from whole saliva of patients presenting signs of oral candidosis were assayed for quantification of colony forming units, exoenzyme activity (phospholipase and proteinase) and antifungal drug sensitivity (amphotericin B, fluconazole and itraconazole) by the reference method of the Clinical and Laboratory Standards Institute. The number of colony forming units per milliliter varied according to the Candida species involved and whether a single or mixed infection was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
8

Year Published

2009
2009
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 23 publications
0
23
0
8
Order By: Relevance
“…This frequency of oral yeast carriage and oral candidiasis varied according to different studies. The difference in sampling preparation and position, treatment conditions of the patients, and geographic area may contribute to the diversity of frequency (Rodu et al, 1984;da Costa et al, 2009). More and more researches indicated that heterogeneity of phenotype and genotype among the population of microorganisms (Wimpenny et al, 2000;Kontoyiannis and Lewis, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…This frequency of oral yeast carriage and oral candidiasis varied according to different studies. The difference in sampling preparation and position, treatment conditions of the patients, and geographic area may contribute to the diversity of frequency (Rodu et al, 1984;da Costa et al, 2009). More and more researches indicated that heterogeneity of phenotype and genotype among the population of microorganisms (Wimpenny et al, 2000;Kontoyiannis and Lewis, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Em concordância com os resultados de Hamza e cols 13 Candida albicans foi a espécie mais frequentemente isolada a partir de infecções do trato respiratório, seguida por Candida glabrata e Candida krusei, demonstrando que a emergência de espécies não-albicans tem produzido efeito relevante nas condutas clínicas 9 . Estudo comparativo de infecções disseminadas em pacientes imunocomprometidos verificou que a taxa de mortalidade associada com Candida krusei foi de 49%, se comparada à taxa de apenas 28% por Candida albicans 8 .…”
Section: Discussionunclassified
“…Quando utilizada em grandes doses orais (excedendo cinco milhões de unidades diárias) pode causar diarreia, distúrbios gastrintestinais, náuseas e vômitos [5,59], sintomas importantes para pacientes que recebem quimioterapia ou imunossupressão [6]. [60].…”
Section: Manifestações Clínicas Da Doençaunclassified
“…Algumas espécies, como C. krusei, C. lusitaniae e C. glabrata, são resistentes a dois ou três agentes antifúngicos e isto pode limitar severamente as opções terapêuticas [16,60,63,66]. Portanto, o desenvolvimento de terapias alternativas aos antifúngicos é de extrema importância nestes casos [33,63,67].…”
Section: Manifestações Clínicas Da Doençaunclassified
See 1 more Smart Citation